European offshore wind capital cost trends up to 2020. (June 2019) - Vieira, M.; Snyder, B.; Henriques, E.; Reis, L.
Abstract: Offshore wind capacity has increased significantly over the past decade with 16 GW installed by the end of 2017. Offshore wind technologies present an effective tool for EU countries to address their renewable production targets, as extensive areas of high winds are available offshore. However, offshore wind is not yet cost competitive in European electricity markets, and frequently requires support schemes to finance extensive capital cost requirements. Therefore, capital cost reductions are critical to make offshore wind technologies competitive in the market. Here, a benchmark tool to analyze capital expenditure trends associated with offshore wind implementation in Europe up to 2020 is provided. A database of all existing farms was developed, detailing more than 21 GW of already commissioned or consented capacity, and trends were described using multiple linear regression models. Results indicate that following a consistent rise from 2000 to 2015, capital costs have since begun to decline. The impact of several farm parameters such as turbine capacity, average farm depth or farm location on the capital expenditures have been estimated. Highlights: Database of 95 European farms was used to evaluate CAPEX trends. Capacity, distance to shore and average farm depth correlate with bigger farm CAPEX. Turbine Capacity and Gravity-based foundations contribute for CAPEX reduction. CAPEX/MW per Year trend revealed influences of non-technical cost drivers.